Quantitative investigation of acceleration due to gravity using PhET interactive simulations in physics education - Fayzullayev, Amirzoda; To’rayev, Quvonchbek; Khushnazarov, Otabek; Mamatkulova, Khadicha; Abdimuminov, Akmal (Universitas Islam Negeri Raden Intan Lampung, 2026)
Understanding acceleration due to gravity (g) is a cornerstone of classical mechanics, but it can be difficult for some students. Traditional experiments often require expensive equipment and are prone to measurement errors. This paper investigated acceleration due to gravity by analyzing the relationship between a projectile's launch angle (θ) and its horizontal range (R). Using PhET simulations, a projectile is launched at various angles while maintaining a constant initial velocity of 15 m/s. Experiments show that the horizontal range depends on the sine of twice the launch angle (sin(2θ)), as predicted by the theoretical equation. This study was quasi-experimental, using a post-test-only design. Twenty high school students participated and were divided into five groups. The experimental results agreed with the linear relationship between R and sin(2θ), allowing g to be approximately 9.81, which is consistent with the accepted value. The average percentage error was only 1.04%, confirming the reliability and accuracy of the PhET simulations. This paper recommends extending the experiments to incorporate real-world settings that account for air resistance and other environmental factors. These findings highlight the effectiveness of simulations in understanding projectile motion and verifying fundamental constants with high precision and minimal equipment.